A phenol/chloroform-free method to extract nucleic acids from recalcitrant, woody tropical species for gene expression and sequencing - François F. Barbier (Plant Methods, 2019)
Abstract Background Woody tropical plants contain high levels of complex organic compounds that inhibit the chemical procedures needed to extract RNA or DNA, thus compromising downstream applications such as RNA sequencing and analysis of gene expression. To overcome this issue, researchers must use extraction protocols using CTAB/PVP buffer instead of commercially available DNA/RNA extraction kits. However, these protocols are time-consuming, use toxic chemicals like phenol and chloroform, and can only be used to process a small number of samples at a time. To overcome these issues, we developed a new CTAB/PVP based protocol for RNA or DNA extraction that eliminates the traditional phenol/chloroform step. Furthermore, the protocol was developed for 96-well plates to speed up processing. Results Our new protocol enabled us to successfully extract RNA from macadamia, avocado, and mango tissues that are traditionally difficult to work with. This RNA was then successfully used to synthesise cDNA for real-time quantitative PCR and to generate good quality RNA-Seq libraries. Our protocol can be easily converted for rapid DNA extraction from different tropical and sub-tropical tree species. Conclusion This method enables safer and faster DNA and RNA extraction from recalcitrant species, thus facilitating future work on tropical trees.